KOMORBID (HIPERTENSI, DIABETES MELLITUS, PENYAKIT KARDIOVASKULAR) DAN KEMATIAN PASIEN COVID-19 - Ananda Iqbal Fanany; Theresia Desy Askitosari; Puri Safitri Hanum (CALYPTRA, 2022)
Abstract—COVID-19 is a disease caused by SARS-CoV-2. Indonesia recorded a total 2,455,912 cases with 64,631 deaths on July 9, 2021. The prevalence in Blitar Regency was 6661 cases with 852 deaths. COVID-19 with comorbidities have risk of falling into severe conditions. The purpose of this study is to determine the relationship between comorbidities and mortality rate of COVID-19 patients at Ngudi Waluyo Hospital, Blitar Regency, April 2020–September 2021. This research is descriptive retrospective with univariate and bivariate analysis. The sample size used total sampling of 677 patients. The distribution of patients died from COVID19 with comorbidities (cardiovascular disease, hypertension, diabetes mellitus) found the highest distribution in 51-60 age group (29.5%), female(51%), working (82.1%). Distribution by comorbid: COVID-19 with comorbidities (78.9%), cardiovascular disease (32.8%), hypertension (30%), diabetes mellitus (16.1%). The result showed a significant relationship between comorbidities (p=0.000), cardiovascular disease (p=0.000), hypertension (p=0.000), diabetes mellitus (p=0.000) and mortality rate of COVID-19. Most of the patients who died from COVID-19 were women aged 51-60 years, worked. There was a weak correlation between the distribution of comorbid cardiovascular disease, hypertension, and diabetes mellitus with the mortality rate of COVID-19 patients and moderate correlation between comorbid with mortality rate of COVID-19 patients. Keywords: blitar regency, comorbid, covid-19, death Abstrak—COVID-19 disebabkan oleh virus SARS-CoV-2. Indonesia terdapat 2,455,912 kasus konfirmasi dengan 64,631 kematian pada 9 Juli 2021. Kabupaten Blitar terdapat 6661 kasus konfirmasi dengan 852 kematian. Pasien COVID-19 disertai komorbid memiliki resiko untuk jatuh ke kondisi yang lebih parah. Penelitian ini bertujuan untuk mengetahui hubungan komorbid dengan angka kematian COVID-19 di RSUD Ngudi Waluyo Kabupaten Blitar Periode Bulan April 2020–September 2021. Penelitian ini bersifat deskriptif retrospektif dengan analisa univariat dan bivariat. Besar sampel menggunakan total sampling sebanyak 677 pasien. Distribusi proporsi pasien meninggal COVID19 dengan komorbid (hipertensi, diabetes Mellitus, penyakit kardiovaskular) di RSUD Ngudi Waluyo Kabupaten Blitar periode Bulan April 2020 – September 2021 ditemukan distribusi tertinggi pada umur 51-60 (29,5%), perempuan (51%), bekerja (82,1%). Distribusi berdasarkan komorbid : COVID-19 meninggal dengan komorbid (78,9%), penyakit kardiovaskular (32,8%), hipertensi (30%), diabetes mellitus (16,1%). Hasil uji statistik didapatkan hubungan signifikan antara komorbid (p=0,000), penyakit kardiovaskular (p=0,000), hipertensi (p=0,000), diabetes mellitus (p=0,000) dengan angka kematian pasien COVID-19. Penelitian ini menunjukkan bahwa pasien meninggal COVID-19 banyak pada perempuan usia 51-60 tahun, bekerja. Terdapat korelasi lemah antara distribusi komorbid penyakit kardiovaskular, hipertensi, diabetes mellitus dengan angka kematian pasien COVID-19. Didapatkan korelasi sedang antara distribusi komorbid dengan angka kematian pasien COVID-19. Kata Kunci: covid-19, kabupaten blitar , kematian, komorbid